Bounds for nonlinear eigenvalue problems - Rafael D. Benguria; M. Cristina Depassier (Electronic Journal of Differential Equations, 2001)
We develop a technique for obtaining bounds on bifurcation curves of nonlinear boundary-value problems defined through nonlinear elliptic partial differential equations.